Maternal Health in Women with Gestational Diabetes: Impact on Neonatal Health and Long-Term Outcomes - Henrique Mendes Rezende, Eduardo; Silvio Fernandes Filho; Stefânia Domingos de Deus; Aline Moreira Moraes; Durval José dos Santos Filho (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Gestational diabetes is a condition affecting an increasing number of women during pregnancy, characterized by elevated blood glucose levels that were not previously diagnosed. This disorder not only has significant implications for maternal health but can also adversely impact neonatal health. Existing literature suggests that women with gestational diabetes face a higher risk of complications during pregnancy, including hypertension and preterm birth, which can, in turn, affect neonatal outcomes and the long-term health of the newborns. Understanding the effects of gestational diabetes is crucial for developing effective preventive and interventional strategies. Objective: Review was to assess the impact of gestational diabetes on neonatal health and the long-term outcomes associated with this condition. Methodology: The methodology followed the PRISMA checklist to ensure transparency and quality in the review process. Relevant databases, including PubMed, Scielo, and Web of Science, were searched. The following descriptors were used: "gestational diabetes," "neonatal health," "long-term outcomes," "maternal health," and "complications." Articles published in the past 10 years that directly addressed the impacts of gestational diabetes were included. Inclusion Criteria: Studies involving women diagnosed with gestational diabetes and their neonates. Articles discussing the effects of the condition on neonatal health and long-term outcomes. Peer-reviewed publications available in English, Portuguese, or Spanish. Exclusion Criteria: Studies focused on type 1 or type 2 diabetes with no direct connection to gestational diabetes. Articles that did not provide relevant data on neonatal health or long-term outcomes. Publications older than a decade or not peer-reviewed. Results: The results indicated that gestational diabetes is associated with a significant increase in the risk of neonatal complications, such as respiratory disorders and low birth weight. Additionally, neonates of mothers with gestational diabetes had a higher likelihood of developing metabolic and cardiovascular issues later in life. The review also highlighted that effective management of gestational diabetes could mitigate some of these risks, improving outcomes for both mothers and their babies. Conclusion: The review underscored the importance of monitoring and managing gestational diabetes to minimize its negative consequences on neonatal health and long-term outcomes. Evidence suggests that early intervention strategies and ongoing care are essential for improving outcomes for mothers and babies affected by this condition.